2012
DOI: 10.26719/2012.18.11.1086
|View full text |Cite
|
Sign up to set email alerts
|

1086 WHO/INRUD patient care and facility-specific drug use indicators at primary health care centres in Eastern province, Saudi Arabia

Abstract: This study aimed to measure the performance of primary health care centres in Eastern province, Saudi Arabia, using the WHO/International Network of Rational Use of Drugs patient care and facility-specific drug use indicators. In a cross-sectional study, 10 health centres were selected using systematic random sampling. A total of 300 patients were interviewed while visiting the centre from January to March 2011 and 10 pharmacists from the same centres were interviewed. Average consultation time was 7.3 min (op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
47
8
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(77 citation statements)
references
References 9 publications
15
47
8
6
Order By: Relevance
“…The proportion of prescribed medicines actually dispensed to patients was 77,1%. Studies performed in Brazil 2 and in Saudi Arabia 4 found higher values for medicines dispensed. The patients who had at least one medicine stockout in PHC unit showed more chance of not receiving at least one medicine prescribed, illustrating negative impact of shortage on patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proportion of prescribed medicines actually dispensed to patients was 77,1%. Studies performed in Brazil 2 and in Saudi Arabia 4 found higher values for medicines dispensed. The patients who had at least one medicine stockout in PHC unit showed more chance of not receiving at least one medicine prescribed, illustrating negative impact of shortage on patients.…”
Section: Discussionmentioning
confidence: 99%
“…This value was higher than that reported in a study conducted at PHC facilities in Brazil 2 and in Saudi Arabia (59,2%). 4 This situation should be observed considering organization of process of selection and distribution of medicines in Belo Horizonte municipality and considering the use of computerized system, facilitating replacement of products and avoiding shortage. The proportion of prescribed medicines actually dispensed to patients was 77,1%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rekomendasi ratarata waktu konsultasi untuk penelitian ini adalah 60 detik. 9 Namun, dari hasil penelitian ini diperoleh hasil rata-rata waktu konsultasi yang melebihi waktu konsultasi yang telah direkomendasikan, yaitu 99,03 detik. Waktu konsultasi oleh apoteker bervariasi mulai dari 10 detik hingga 370 detik, bergantung pada banyaknya informasi mengenai obat yang harus disampaikan serta pemahaman pasien.…”
Section: Pembahasanunclassified
“…In the eastern part of Saudi Arabia, the average drug dispensing time is 100 (58-180) seconds (6) and in Egypt (Alexandria) it is less than 60 (47.4) seconds (7). In Kragujevac, the average drug dispensing time was between 20.4 and 48.2 seconds, and times were longer in private pharmacies (8).…”
Section: Introductionmentioning
confidence: 99%